The Effect of Statins on Clinical Outcome Among Hospitalized Patients With COVID-19: A Multi-Centric Cohort Study - Umakanthan, Srikanth; Senthil, Sanjum; John, Stanley; Madhavan, Mahesh K.; Das, Jessica; Patil, Sonal; Rameshwaram, Raghunath; Cintham, Ananya; Subramaniam, Venkatesh; Yogi, Madhusudan; Bansal, Abhishek; Achutham, Sumesh; et al. (Frontiers in Pharmacology, 2022)
The coronavirus disease-2019 (COVID-19) is caused by SARS-CoV-2, leading to acute respiratory distress syndrome (ARDS), thrombotic complications, and myocardial injury. Statins, prescribed for lipid reduction, have anti-inflammatory, anti-thrombotic, and immunomodulatory properties and are associated with reduced mortality rates in COVID-19 patients. Our goal was to investigate the beneficial effects of statins in hospitalized COVID-19 patients admitted to three multi-specialty hospitals in India from 1 June 2020, to 30 April 2021. This retrospective study included 1,626 patients, of which 524 (32.2%) were antecedent statin users among 768 patients (384 statin users, 384 non-statin users) identified with 1:1 propensity-score matching. We established a multivariable logistic regression model to identify the patients’ demographics and adjust the baseline clinical and laboratory characteristics and co-morbidities. Statin users showed a lower mean of white blood cell count (7.6 × 103/µL vs. 8.1 × 103/µL, p < 0.01), and C-reactive protein (100 mg/L vs. 120.7 mg/L, p < 0.001) compared to non-statin COVID-19 patients. The same positive results followed in lipid profiles for patients on statins. Cox proportional-hazards regression models evaluated the association between statin use and mortality rate. The primary endpoint involved mortality during the hospital stay. Statin use was associated with lower odds of mortality in the propensity-matched cohort (OR 0.52, 95% CI 0.33-0.64, p < 0.001). These results support the previous evidence of the beneficial effects of statins in reducing mortality in hospitalized COVID-19 patients.